THE RULE OF LAW, THE SEPARATION OF POWERS, AND BIG TECH - Sahadzic, Maja (Pravni zapisi, 2025)
The growing influence of Big Tech, backed by technological advancement and platformization, poses significant challenges to traditional concepts of the rule of law and the separation of powers. By privately accumulating functions typically reserved for the state, Big Tech now assumes functions traditionally assigned to the state. In light of this, this paper explores the limitations imposed on the rule of law and the separation of powers. It first revisits the classical understanding of these constitutional principles and then assesses the contemporary challenges posed by Big Tech. The analysis then shifts to the rising private (technological) power of Big Tech as a fourth pillar in the separation of powers. Finally, the paper argues for cooperation and coordinated governance between the state and Big Tech, ultimately concluding with final insights on the adaptiveness of the traditional concepts of the rule of law and the separation of powers.